Screening for Autoimmune Markers Is Unnecessary during Follow-up of Adults with Autoimmune Thrombocytopenic Purpura and no Autoimmune Markers at Onset - Vantelon, J. M.; Godeau, B.; André, C.; Bierling, P. (Thrombosis and Haemostasis, 2000)
In an attempt to evaluate the frequency of autoimmune markers in autoimmune thrombocytopenic purpura (AITP) and to determine if autoimmune markers in patients with isolated AITP were associated with particular disease manifestations, we analyzed records of 122 consecutive adults with AITP. Twenty-nine patients (24%) had significant titers of one or several autoimmune markers at AITP onset. Among them, 16 (13%) had antinuclear antibodies. The presence of autoimmune markers did not correlate with presenting feature, response to treatment or long-term outcome of AITP. Six patients (5%) developed seven autoimmune diseases during follow-up, comprising systemic lupus erythematosus, an antiphospholipid syndrome, autoimmune haemolytic anemia (n = 2), Grave’s disease, Hashimoto’s disease and primary biliary cirrhosis. At AITP onset, three of these patients had isolated biological markers of the autoimmune disease they later developed. The annual average incidence rate of autoimmune diseases was 1% per patient-year in the entire group and 0.4% in the group of patients with no autoimmune markers at AITP onset. This low rate is probably due to careful assessment at diagnosis for concomitant overt autoimmune disease. We recommend extensive screening for autoimmune markers at AITP onset, and careful follow-up of patients with autoimmune markers. Routine screening for autoimmune markers during AITP follow-up is not necessary for patients with no autoimmune markers at AITP onset.Systemic lupus erythematosus (SLE) and other autoimmune disorders can complicate autoimmune thrombocytopenic purpura (AITP) or be diagnosed concomitantly with otherwise unremarkable AITP (1, 2). However, the frequency and prognostic value of isolated autoimmune markers (i. e. not associated with an autoimmune disorder), particularly antinuclear antibodies (ANA) at AITP onset or during follow-up is controversial (3-8). For example, the committee organized by George et al. (9) to write guideline on the diagnosis and treatment of AITP stated that the search for ANA and lupus anticoagulant were of “uncertain appropriateness at diagnosis and during follow-up”. In an attempt to help practicians to make decisions, we analyzed the frequency of autoimmune markers and autoimmune disorders at onset and during the follow-up in 122 adults with AITP and no overt autoimmune disease at diagnosis. These consecutive patients were followed by the same physician for a mean period of 6 years, and had routine screening tests for autoimmune markers and disorders at onset, before steroid therapy, and regularly during follow-up.
Keywords: Autoimmune thrombocytopenic purpura; autoantibody; antinuclear antibody; systemic lupus erythematosus